Black Moth - Heyer, Georgette (Naperville, Ill. Sourcebooks Casablanca, 2009)
"Seven years before our story opens, Carstares protected his brother by allowing himself to be disgraced for cheating at cards. His brother, suffering intense guilt, isn't aware that they played right into the hands of the Duke of Andover. The disgraced Earl now roams the countryside until a confrontation with his rival thwarts the attempt to kidnap the lovely Diana. But now the Duke is more determined than ever to have Diana for his own, and the two men will meet at sword point before the Earl's name can be cleared and he can claim his fair lady"--Publisher's Web site.
105527
Keywords: Aristocracy (Social class) -- England -- Fiction; Romance fiction; Fiction; Regency fiction; Love stories